2012
DOI: 10.1097/adm.0b013e3182548abd
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Experiential Curriculum for Addiction Education Among Medical Students

Abstract: Undergraduate medical educational interventions combining traditional and experiential programming may render participants better equipped than peers receiving only traditional education to address addiction as physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 12 publications
5
33
0
2
Order By: Relevance
“…This seems to coincide with other studies remarking the importance of training (Barron et al, 2012a;Karam-Hage et al, 2001). In contrast, year of training did not correlate with any of the other dimensions.…”
Section: Discussionsupporting
confidence: 72%
“…This seems to coincide with other studies remarking the importance of training (Barron et al, 2012a;Karam-Hage et al, 2001). In contrast, year of training did not correlate with any of the other dimensions.…”
Section: Discussionsupporting
confidence: 72%
“…Several studies have shown that even short courses could increase knowledge on addiction medicine [36,37,38,39,40]. Moreover, courses have also been shown to induce more professional perceptions of and attitude toward patients with SUDs [36,37,38,39,41,42,43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, courses have also been shown to induce more professional perceptions of and attitude toward patients with SUDs [36,37,38,39,41,42,43,44]. These studies cover the full range of undergraduate level [32,36,38,40], general physician level [37,39,40,42,43,44,45] and addiction specialist level [41]. However, several questions remain unanswered: What teaching methods are most effective in improving knowledge, skills and attitude related to addiction medicine and what should an addiction medicine curriculum comprise?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attendants of universities are one of the most valuable and important parts of medical science universities (1). Duties expected of each attendant in these universities are categorized into seven sections: instruction, research, visiting patients, management, professional activities out of the university, personal promotion and civil activity (2).…”
Section: Introductionmentioning
confidence: 99%